(untitled) (CAHIERS MAGELLANES-NS, 2024)
The northeast region of India has always been considered the most unexplored and unfamiliar part of the country. Despite being an integral part of India, the northeast has often been seen as the "other" and has remained on the periphery of mainstream society. This region is highly diverse, comprising eight states: Assam, Arunachal Pradesh, Meghalaya, Manipur, Mizoram, Tripura, Nagaland, and Sikkim. However, the contributions of this region to mainstream literature have been historically overlooked. The voices emerging from the northeast not only represent the marginalized and often neglected region, but also embody dissent. Despite facing numerous challenges, writers from the northeast are carving out their own spaces in the literary world. Figures such as Mamang Dai and Temsula Ao are becoming synonymous with the representation of their entire community and are offering fresh perspectives to the literary scene. Their poetry has opened new horizons of interpretation and understanding, breathing new life into the previously unrecognized domain of literature. These writers from India’s northeast have played a crucial role in bringing recognition to the previously overlooked literature of the region. Through their works, Temsula Ao and Mamang Dai explore and articulate themes of representation, identity, and power, showcasing voices and perspectives of dissent, criticism, and introspection.